2009
DOI: 10.3354/dao02100
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of New Zealand Greenshell™ mussel Perna canaliculus larvae using two Vibrio pathogens: a hatchery study

Abstract: Bacterial diseases remain a large problem in aquaculture hatcheries. The successful design and implementation of protective measures in the hatchery depends on an understanding of the dynamics of the infection process. Developing an in situ experimental protocol for pathogen challenge is therefore of paramount importance. Here, we demonstrated the minimum effective pathogenic dose (MEPD) of Vibrio splendidus (10 5 CFU ml -1) and a Vibrio coralliilyticus/neptunius-like isolate, Vibrio sp. DO1 (10 6 CFU ml -1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…; Kesarcodi‐Watson et al . ). In only 6 days, these strains became dominant in larvae and sea water, and this status was maintained until the collapse of batch B .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Kesarcodi‐Watson et al . ). In only 6 days, these strains became dominant in larvae and sea water, and this status was maintained until the collapse of batch B .…”
Section: Discussionmentioning
confidence: 97%
“…; Kesarcodi‐Watson et al . ). These studies reported the disease in a wide range of bivalve species, including oysters ( Ostrea , Crassostrea ), clams ( Mercenaria , Venerupis , Panope ), scallops ( Pecten , Argopecten ) and mussels ( Perna ).…”
Section: Introductionmentioning
confidence: 97%
“…The work of Prado and co-workers constituted the first description of V. neptunius as a molluscan pathogen. Later studies with New Zealand Greenshell mussel ( Perna canaliculus ) larvae confirmed the pathogenic potential for other molluscan species (Kesarcodi-Watson et al, 2009a,b). …”
Section: New Vibrio Species Associated To Molluscsmentioning
confidence: 88%
“…Initially described in association with diseased corals (Vezzulli et al, 2010), V. coralliilyticus was isolated from mortality episodes of Greenshell mussels (Kesarcodi-Watson et al, 2009a) and oysters (Hada et al, 1984), and was shown to be virulent to larval stages of those species (Kesarcodi-Watson et al, 2009b;Genard et al, 2013).…”
Section: Coralliilyticusmentioning
confidence: 99%
“…These include irregular movements, detachment of cilia, aggregation of bacteria around the velum and deterioration of soft tissues (Kesarcodi-Watson et al, 2009a) (Figure 3,Table 1). V. coralliilyticus exposure resulted in reduced feeding activity of oyster larvae, fatty acid remodeling of polar lipids, activation of defenses (antioxidant and immune defenses)(Genard et al, 2013) and larval bivalve mortality(Kesarcodi-Watson et al, 2009a;Kesarcodi-Watson et al, 2009b;Genard et al, 2013;Mersni Achour et al, 2015).…”
mentioning
confidence: 99%